Analisis Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan (Studi Kasus Pada Bengkel Servis Motor AHASS Honda Universitas Muhammadiyah Surakarta) - Abidin, Nurul; , Kusdiyanto, S.E., M.Si (2015)
This study aims to examine the effect of service quality and price toward customer satisfaction. This study uses a quantitative associative method using statistical analysis to examine the hypothesis. The population of the study is all customer services of AHASS Honda motorcycle at Muhammadiyah University of Surakarta. The sample is taken 100 respondents and data source is primary data obtained by distributing questionnaires. Method of analyzing data research uses multiple linear regression, whereas the hypothesis test is t-test, f-test, and the coefficient of determination R Square. The result of multiple linear regression shows that the service quality and price influential the significant on customer satisfaction. The result of t-test means the service quality and acceptable price and significant impact on customer satisfaction. The result of f-test concldes that cillectively the service quality and price influential the significant on customer satisfaction.